Antibiotic susceptibility profile of Acinetobacter isolates isolated from various clinical specimens received at a tertiary care hospital in North western region of Gujarat - Hitesh Assudani; Thiyagarajan Brihadishwwaran; Krunal Mehta; Krupali Kothari; Shilpa Supekar; Dolly Solanki (GAIMS Journal of Medical Sciences, 2022)
Introduction: Acinetobacter species has now been identified as a prime and notorious cause of nosocomial pneumonia and bloodstream infections, which is been observed especially among immunocompromised patients with underlying co morbidities or deliberating illnesses. Globally, there has been a significant increase in resistance of this organism to most of the antimicrobials in recent period.